Finite Difference Method Applied to an Unsteady Magnetohydrodynamic Newtonian Fluid with Wall Slip in Darcy-Forchheimer Porous Medium - Funmilayo H, Oyelami; Abdulwaheed, Jimoh; O.Y, Saka-Balogun (International Journal of Mathematical Research, 2016)
This study investigated the effects of magnetic field, thermal radiation and wall slip on a Newtonian, incompressible, viscous fluid flowing through a saturated porous medium. Boundary conditions for slip at the wall hold in the fluid. The governing equations are formulated, simplified and non-dimensionalised. The dimensionless equations were solved with the help of Crank Nicolson’s finite difference method. This method converges faster and it is unconditionally stable. Numerical results are presented with the aid of graph to account for the fluid parameters affecting the flow on velocity and temperature profiles.